Advances in the identification and characterization of molecular factors related with resistance of the Phaseolus lunatus to Acanthoscelides obtectus (Coleoptera: Bruchidae) - FORY, LUISA FERNANDO; ANGEL, FERNANDO; THOME, JOE; CARDONA, CÉSAR; ROCA, WILLIAM (Revista Colombiana de Entomología, 1998)
For the development of improved bean liaises resistant to Acanthoscelides obtectus (Say), an important bean storage insect pest, it is indispensible to elucidate the genes involved in antibiotic resistance. The RNA differential display technique is a useful tool in the isolation of genes that show differential expression in different tissues. Up to this moment we have implemented both radioactive, and non-radioactive techniques. Total RNA has been isolated from different genotypes of P lunatus with varying levels of resistance to A. obtectus and then bulked into groups of resistant and susceptible genotypes. The messenger RNA (protein-coding sequence) was isolated by chromatography and used in reverse transcription experiments. Hexanucleotide primers were used for the first-strand synthesis and the amplification of cDNAs was done through the polymerase chain reaction (PCR). The synthesis of the second strand was performed using random primers ten nucleotides in length each. The isolated bands were confirmed through the differential display of total RNA in each of the genotypes. The evaluation of 76 random decanucleotides has made evident 6 differential bands sized between 200 and 600 bp. The purified amplified bands were assessed against resistant and susceptible genotypes through northern blots. Bands present in resistant genotypes have been reamplified and cloned in pCRII plasmids. Simultaneously, other experiments have been developed to identify factors involved in resistance through subtractive hybridization and the use of degenerate primers.